The Training of the Future Music Teacher in an Orchestra Class According to the Demands of the Credit and Module System - Plyachenko, T.N. (Pedagogy of Higher and Secondary Education, 2007)
In the article by the content of the educational program is revealed in an orchestra class students of the Department of Art of the Pedagogical University, who study according to the credit and module educational system.